Legitimacy and Rationalization in European Criminal Law: A Critical Analysis of the Criminalization of Migrant Smuggling - Raquel Cardoso (University of Bologna Law Review)
The article critically examines the legitimacy of European criminal law through the perspective of migrant smuggling incrimination. By analyzing the complex intersection of legal principles and migration policies, the research investigates whether applying a principled criminalization approach can resolve existing systemic legitimacy challenges in European criminal law. The study systematically deconstructs migrant smuggling as a legal concept, evaluates its alignment with broader criminal law functions, and critically assesses the legal and ethical implications of current European Union incrimination strategies. Through a comprehensive methodology examining normative frameworks, interests, and legal principles, the research aims to provide a nuanced evaluation of criminal law rationalization in the European context. After defining the conduct and differentiating it from related concepts in the Introduction, Section 1 explores the relationship between migrant smuggling and the functions of European criminal law. Section 2 undertakes a step-by-step analysis of the criminalization process, examining all relevant interests and principles. Section 3 critically assesses the adequacy of this process’s outcomes, followed by concluding observations on the broader implications for European criminal law legitimacy.